The Trinity and Communal Spirituality: Understanding The Nicene Creed in The Asian Context - Petrus Simarmata (Fakultas Teologi, Universitas Sanata Dharma, 2025)
The Nicene Creed (325), which affirms the Trinity as the core of Christian faith with profound theological, spiritual, and social ramifications, holds particular significance within the Asian context. This qualitative study employs a literature review to analyse the intricate relationship between the doctrine of the Trinity and communal spirituality in Asia. A comprehensive review of theological sources was undertaken, and the results demonstrate how the Trinitarian understanding of the Father, Son, and Holy Spirit's relationality inspires a communal ethos characterised by solidarity, harmony, and togetherness. Within Asian traditions, which are deeply rooted in values of collectivity and interrelational spirituality, the doctrine of the Trinity emerges as a potent paradigm for an inclusive and dialogical expression of faith. The study thus substantiates the conclusion that the Nicene Creed, in addition to its dogmatic function, possesses the power to effect transformation in the practical realm of Christian communal life throughout Asia.